A Comparative Study of Hip Arthroplasty and Closed Reduction Proximal Femur Nail in the Treatment of Elderly Patients with Hip Fractures - Zhou, Xianchao; Shen, Xiang (Frontiers in Surgery, 2022)
Objective: To compare the clinical effect of hip arthroplasty and closed reduction intramedullary nailing of proximal femur in the treatment of elderly hip fractures patients. Methods: There are 90 elderly hip fracture patients being recruited in the present study. 50 patients in Group A received closed reduction intramedullary nailing of proximal femur, and 40 patients in Group B received hip arthroplasty. All patients were followed up for 12 months after surgery, clinical outcomes included surgical indicators, VAS score, Harris score, quality of life, mental status, and complications. Results: The surgery time, bleeding volume, infusion volume of patients in Group A are all significantly lower than those in Group B (P<0.05), while the weight-bearing activity time and first workout time of Group A are all significantly higher than those in Group B (P<0.05). The VAS score in patients of Group A at 1 weeks postoperative is significantly lower than that in patients of Group B (P<0.05). The Harris score in patients of Group A at 3 months, 6 months and 12 months postoperative are all significantly higher than those in patients of Group B (P<0.05), and the excellent and good rate of hip function recovery at 12 months postoperative in patient of Group A is significantly lower than that in patients of Group B (80% vs 95%, P<0.05). Furthermore, The score of SF-36 (PCS), SF-36 (MCS) and Barthel in patients of Group A at 6 months postoperative are significantly lower than those in patients of Group B (P<0.05), and the score of MMSE is significantly higher (P<0.05), while there are not significantly different at 12 months postoperative (P>0.05). The incidence of postoperative complications in Group A was significantly lower than that in Group B (10% vs 27.5%, P<0.05). Conclusion: Elderly hip fracture patients treated with closed reduction intramedullary nailing of proximal femur has less surgical trauma and lower complication rates, but slower postoperative recovery compared with closed reduction intramedullary nailing of proximal femur.